Ethics of split liver transplantation: should a large liver always be split if medically safe?. Issue 10 (9th July 2021) - Kim, Tae Wan; Roberts, John; Strudler, Alan; Tayur, Sridhar
Abstract : Split liver transplantation (SLT) provides an opportunity to divide a donor liver, offering transplants to two small patients (one or both could be a child) rather than keeping it whole and providing a transplant to a single larger adult patient. In this article, we attempt to address the following question that is identified by the Organ Procurement and Transplant Network and United Network for Organ Sharing: 'Should a large liver always be split if medically safe?' This article aims to defend an answer—'not always'—and clarify under what circumstances SLT is ethically desirable. Our answer will show why a more dynamic approach is needed to the ethics of SLT. First, we discuss a case that does not need a dynamic approach. Then, we explain what is meant by a dynamic approach and why it is needed.